Strategi interaksi dalam tradisi lisan Isun-Isun Bajau - Saidatul Nornis Hj. Mahali, (Universiti Kebangsaan Malaysia, 2008)
Everyday we use language to interact with one other. There are various ways in which we interact, either directly or indirectly. The speaker and listener require some prior knowledge of the ideas that need to be communicated to avoid possible miscommunication. Bajau people in Kota Belud, Sabah, use a form of communication called Isun-Isun which is an oral folk tradition that is sung. These songs employ several interaction strategies, such as assimilation, reassurance and statement to avoid possible miscommunication and misunderstanding. Isun-Isun is a fine example of the formal art of communicating that is often uncovered in oral traditions